2006
DOI: 10.1242/jeb.02418
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic modulation of respiratory motor output during tadpole development: role of α-adrenoceptors

Abstract: Noradrenaline (NA) is an important modulator of respiratory activity. Results from in vitro studies using immature rodents suggest that the effects exerted by NA change during development, but these investigations have been limited to neonatal stages. To address this issue, we used in vitro brainstem preparations of an ectotherm, Rana catesbeiana, at three developmental stages: premetamorphic tadpoles, metamorphic tadpoles and fully mature adult bullfrogs. We first compared the effects of NA bath application (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
4
20
1
Order By: Relevance
“…At this point, little is known about the neural mechanisms underlying the central O 2 chemoreflex in amphibians. While we have recently shown that, under standard (hyperoxic) conditions, NA bath application onto bullfrog brainstem preparations elicits fictive lung ventilation responses that are similar to those observed during hypoxia (Fournier and Kinkead, 2006), a direct involvement of noradrenergic modulation in the O 2 chemoreflex remains to be demonstrated in this species. With that in mind, the main objective of the present study was to better understand the mechanisms underlying the central O 2 chemoreflex by testing the hypothesis that noradrenergic receptor activation is necessary to observe a fictive lung ventilation response to hypoxia in the brainstem preparation from Rana catesbeiana.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…At this point, little is known about the neural mechanisms underlying the central O 2 chemoreflex in amphibians. While we have recently shown that, under standard (hyperoxic) conditions, NA bath application onto bullfrog brainstem preparations elicits fictive lung ventilation responses that are similar to those observed during hypoxia (Fournier and Kinkead, 2006), a direct involvement of noradrenergic modulation in the O 2 chemoreflex remains to be demonstrated in this species. With that in mind, the main objective of the present study was to better understand the mechanisms underlying the central O 2 chemoreflex by testing the hypothesis that noradrenergic receptor activation is necessary to observe a fictive lung ventilation response to hypoxia in the brainstem preparation from Rana catesbeiana.…”
Section: Introductionmentioning
confidence: 93%
“…The brain was irrigated with ice-cold (0-5°C) artificial cerebrospinal fluid (aCSF) to reduce axonal conductance throughout the dissection procedure. The composition of the aCSF was identical to the one used in our previous studies (Kinkead et al, 1994;Kinkead et al, 2002;Fournier and Kinkead, 2006). For tadpoles, the aCSF consisted of (in mmol·l -1 ): 104 NaCl; 4 KCl; 1.4 MgCl 2 ; 10 D-glucose; 25 NaHCO 3 ; 2.4 CaCl 2 , and for adult bullfrogs: 75 NaCl; 4.5 KCl; 1 MgCl 2 ; 7.5 D-glucose; 40 NaHCO 3 ; 2.5 CaCl 2 ; 1 NaH 2 PO 4 .…”
Section: In Vitro Brainstem Preparationsmentioning
confidence: 99%
See 3 more Smart Citations